Implementasi Konsep Lean Manufacturing Guna Mengurangi Pemborosan Di Lantai Produksi Pabrik Bakpia Pathok 25 - Aldiyan, Arif; Kurniawan, Evan; Faisal Nurfaizi, Mohammad; Al-Faritsy, Ari Zaki (DPPM UNIVERSITAS PELITA BANGSA, 2023)
The concept of lean manufacturing was developed to maximize resource utilization through minimizing waste, then lean was developed in response to a fluctuating and competitive business environment. Due to the rapidly changing business environment, organizations are forced to face challenges and complexities. Any manufacturing or service-oriented organization for survival may ultimately depend on its ability to systematically and continuously respond to these changes to increase product value. Because a value adding process is necessary to achieve this perfection, implementing a lean manufacturing system is therefore a core competency for all types of organizations to maintain. Most studies focus on one aspect of lean elements, very few focus on more than one aspect of lean elements, but for successful implementation of lean, organizations must focus on all aspects such as Value Stream Mapping (VSM). In this paper, an attempt has been made to develop a lean route map for organizations to implement lean manufacturing systems. An analysis of the results from an exploratory study compiled in this report to illustrate the sequence of applying lean elements in a volatile business environment. The results from the reviews have been combined to provide a unified theory for applying lean manufacturing concepts.